A Smart Sensing Method for Object Identification Using Circularly Polarized Luminescence from Coordination‐Driven Self‐Assembly. Issue 29 (19th June 2018) - Imai, Yuki; Nakano, Yuka; Kawai, Tsuyoshi; Yuasa, Junpei
Abstract: The potential use of circularly polarized luminescence for object identification in a sensor application is demonstrated. New luminescence probes using pyrene derivatives as sensor luminophores were developed. (R, R)‐Im2 Py and (S, S)‐Im2 Py contain two chiral imidazole moieties at 1, 6‐positions through ethynyl spacers (angle between spacers ca. 180°). The probe molecules spontaneously self‐assemble into chiral stacks (P or M helicity) upon coordination to metal ions with tetrahedral coordination (Zn 2+ ). The chiral probes display neither circular dichroism (CD) nor circularly polarized luminescence (CPL) without metal ions. However, (R, R)‐Im2 Py and (S, S)‐Im2 Py exhibit intense chiroptical activity (CD and CPL) upon self‐assembly with Zn 2+ ions. (R, R)‐Im2 Py and (S, S)‐Im2 Py with chemical stimuli‐responsibility allow sensing using the CPL signal as detection output, enabling us to discriminate between a signal from the target analyte and that from non‐target species. Abstract : Getting it right (or left) : A potential use of circularly polarized luminescence (CPL) for object identification in a sensor is demonstrated. To this aim, new luminescence probes with chiroptical switchability have been developed using pyrene derivatives. Picture: CPL mapping, I L, I R =left, right CPL intensity.